Laying the foundation for software development industry in Zimbabwe - Ruvinga, Caroline; Ruvinga, Lawrence; Zhou, Munyaradzi; Musungwini, Samuel; Zhou, Tinashe Gwendolyn (International Journal of Advanced Research in Computer Science & Technology, 2019)
This paper analyses the impact of the Zimbabwe education curriculum on the development of home grown software solutions. Interviews and questionnaires were employed as information gathering techniques, to obtain both qualitative and quantitative data. This study reveals that, to a greater extent early exposure to computing studies produces high quality software development programmers. The study further reveals that most computing professionals only learn programming basics at advanced stages of career development. This adversely affects the software development industry in Zimbabwe as it runs short of experts in the field. The paper recommends early introduction to programming concepts in primary and secondary education, which will go a long way in career development and ultimately create opportunities in the software development industry and benefit the Zimbabwe economy at large.